1999
DOI: 10.1046/j.1365-294x.1999.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Microevolution, low clonal diversity and genetic affinities of parthenogeneticSitobionaphids in New Zealand

Abstract: In sharp contrast to their southeast Asian and European counterparts, Sitobion miscanthi and S. near fragariae aphids in Australia exhibit a complete absence of sexual reproduction. This demands an explanation within the context of the evolution and maintenance of sex and parthenogenesis. Accordingly, we executed a genetic analysis of the two species in neighbouring New Zealand. Microsatellites and single‐stranded conformation polymorphism/sequence analysis of the nuclear gene elongation factor 1α were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 48 publications
(86 reference statements)
8
109
0
Order By: Relevance
“…As neutral allele sequence divergence tends to increase rapidly in OP lineages that accumulate mutations (Birky, 1996), we expect to find higher levels of heterozygosity if populations have a higher degree of asexuality. In agreement with this, a high heterozygosity level was observed in Sitobion species that were mainly or functionally asexual Simon et al, 1999;Wilson et al, 1999;Haack et al, 2000). The high level of heterozygosity found in the French population of our study further confirms this pattern since we have previously shown that asexual lineages are prevalent in this region (Dedryver et al, 2001).…”
Section: Validation Of Theoretical Modelssupporting
confidence: 91%
See 1 more Smart Citation
“…As neutral allele sequence divergence tends to increase rapidly in OP lineages that accumulate mutations (Birky, 1996), we expect to find higher levels of heterozygosity if populations have a higher degree of asexuality. In agreement with this, a high heterozygosity level was observed in Sitobion species that were mainly or functionally asexual Simon et al, 1999;Wilson et al, 1999;Haack et al, 2000). The high level of heterozygosity found in the French population of our study further confirms this pattern since we have previously shown that asexual lineages are prevalent in this region (Dedryver et al, 2001).…”
Section: Validation Of Theoretical Modelssupporting
confidence: 91%
“…Each aphid was genotyped using five microsatellite loci: four of these (Sm10, Sm17, S16b, and S17b) were isolated from S. miscanthi Simon et al, 1999;Wilson et al, 1999), and one (S5L) was isolated from S. avenae (Simon et al, unpublished).…”
Section: Microsatellite Genotypingmentioning
confidence: 99%
“…Nevertheless, a variety of studies have found evidence for evolution and adaptation occurring in a surprisingly effective manner in asexual populations (eg Parker, 1979a;Williamson, 1981;Glazier, 1992;Christensen et al, 1992;Toline and Lynch, 1994;Andrade and Roitberg, 1995;Sunnucks et al, 1998;Weeks and Hoffman, 1998;Wilson et al, 1999Wilson et al, , 2003. These works cite such evidence as diverse and closely adapted clonal arrays (eg Parker, 1979a-c;Weeks and Hoffman, 1998;Wilson et al, 1999), natural clonal assemblages shown to have high (comparable to sexual) heritabilities for life history, morphological, and fitness-related traits (Stratton, 1991(Stratton, , 1992, and parthenogenetic genotypes that seem to outcompete sympatric sexual forms (eg Browne, 1992;Christensen et al, 1992;Weeks and Hoffman, 1998).…”
Section: Conversion With Physical Limits On Recombination Chromosomalmentioning
confidence: 99%
“…However, of the 15 genotypic classes sampled multiple times, nine were found in more than one vineyard (Table 5). The likelihood of these identical genotypic classes arising in separate locations via independent sexual recombinant events is low, unless there was extremely rare sex with sexual offspring unable to compete successfully against parthenogenic lineages (Lynch, 1984;Wilson et al, 1999;Peck and Waxman, 2000). More intensive intra-vineyard studies (26) 1 (4) 0.540 (4) - (1) - (1) - (1) 0.111 (8) 0.953 (9) 0.392 (5) Alleles = number of alleles; H DC = direct-count heterozygosity; H E = expected heterozygosity (unbiased estimate); P = P-value of the HardyWeinberg exact test; SLP = P-value of the Hardy-Weinberg exact test using only one individual per genotype (based on the rationale of Sunnucks et al, 1997); n = sample size; PL = percentage of polymorphic loci (based on 0.95 criterion); SE = standard error.…”
Section: Population Structurementioning
confidence: 99%
“…As codominant and highly variable DNA markers, they provide a powerful system for unraveling life history traits, particularly the occurrence of sex (reviewed in Sunnucks et al, 1997;Hales et al, 1997). They have been used in life cycle studies of members of the Aphididae family, resulting in high level resolution of reproductive mode and exploration of genetic relationships, including those of clonal lineages (Sunnucks et al, 1996Fuller et al, 1999;Simon et al, 1999;Wilson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%